Ta’thīr Rasm al-Bayānāt al-Nibrīyah ‘alá Natījat Ta‘allum al-Qirā’ah al-Jahrīyah fī Dars al-Qira’āh ‘inda Ṭalabat Qism Ta‘līm al-Lughah al-‘Arabīyah, Jāmi‘at Jākartā al-Ḥukūmīyah - Hendrawanto Ch; Siti Ulfa Fauziah (Al-Ma‘rifah, 2019)
This research aims to know the effect of the intonation diagram on the results of reading aloud learning for students of the Arabic Language Education Study Program, Faculty of Languages and Arts, Universitas Negeri Jakarta. The used method for this research is experimental, and the samples were taken from the students of the Arabic Language Education Study Program 2018 from class A, B, C, and D. The population was 108 students, 56 students in an experimental group, while 52 students in the control group. The conclusion of this research based on this final data. The test results show that the value of T calculated obtain from 0,05 is (3,3) and the value of the T table (1,685) for the degree of freedom (dk=106). Because the obtained T calculated bigger than the value of the T table, then the hypothesis is 0 (H0) rejected and the research hypothesis (H1) accepted. Based on the data, it shows that the effect of the intonation diagram on reading aloud learning has a positive effect, which is one of the learning media that can improve the reading aloud for students of the Arabic Language Education Study Program.